Modeling and simulation of hydraulic wind turbine - Zhang, Yin (2013)
The wind energy can be transferred through an intermediate medium such as hydraulic fluids. In this paper a hydraulic system is utilized to transfer the wind energy from a wind turbine to a synchronous generator. A close loop hydraulic transfer system with fixed displacement pump and variable displacement motor is introduced and the mathematical model is obtained. The simulation of the hydraulic wind turbine is derived by using the SimHydraulics toolbox of MATLAB and AMESim. The simulation results demonstrate the effectiveness of the modeling and are useful to design the control system.